An integrative approach elucidates the systematics of Sea Hayward and Cybdelis Boisduval (Lepidoptera: Nymphalidae: Biblidinae). (3rd January 2019) - Dias, Fernando M. S.; Siewert, Ricardo R.; Freitas, André V. L.; Lamas, Gerardo; Magaldi, Luiza M.; Mielke, Olaf H. H.; Casagrande, Mirna M.
Abstract: The systematics of the enigmatic and rather uncommon species of Sea Hayward and Cybdelis Boisduval is assessed through morphological and molecular analyses. The aim of this paper is three‐fold: (i) to ascertain the phylogenetic position of Sea and Cybdelis in Biblidinae; (ii) to determine the evolutionary relationships among species of Sea and Cybdelis ; and (iii) to review the taxonomy of Sea and Cybdelis . The result of the molecular analysis recovers Sea sister to Cybdelis, and this clade sister to Eubagina (sensu Lamas, 2004 ), rendering Epicaliina (sensu Lamas, 2004 ) paraphyletic. A new tribe, Cybdelinitrib.n. is erected to include Sea and Cybdelis ; the other genera formerly included in Epicaliina (sensu Lamas, 2004 ), Eunica Hübner and Sevenia Koçak are assigned to Eunicinitrib.rest., and the remaining genera of Biblidinae to other previously recognized tribes, similar to those implicitly proposed by Wahlberg et al . (2009 ). The morphological analysis recovers similar results and the following relationships among species of Cybdelis : C. phaesyla (Hübner) ( C. boliviana Salvin ( C. mnasylus Doubleday ( C. petronita Burmeisterstat.rest. + C. thrasylla C. Felder & R. Felderstat.rest. ))). Sea and Cybdelis are recognized as distinct genera; a new subspecies, S. sophronia jenkinsi Dias, Siewert & Freitasssp.n., distributed from Venezuela to Bolivia along the Andes eastern foothills, is described; and C. petronita and C. thrasylla are accepted as valid species. Lectotypes for C. boliviana, C. peruviana Staudinger, C. mnasylus, C. thrasylla, C. petronita and C. mnasylus var. meridionalis Hall and a neotype for Vanessa sophronia Godart are designated. Additionally, dichotomous keys and distribution maps to all taxa are provided; male genitalia and hypandria are illustrated for all species; generic characters of the head, labial palpi and legs are illustrated; immature stages of some species also are figured. The published work has been registered on ZooBank:http://zoobank.org/urn:lsid:zoobank.org:pub:D8EBB649‐5E9D‐4218‐B1F1‐7A69DA775FD0 . Abstract : Molecular analysis recovers the validity of the sister genera Sea and Cybdelis, and this clade as sister to Eubagina, rendering Epicaliina (sensu Lamas, 2004 ) paraphyletic. Cybdelinitrib.n. includes Sea and Cybdelis, other genera formerly in Epicaliina (sensu Lamas, 2004 ) are assigned to Eunicinitrib.rest., and the remaining genera to other previously recognized tribes. Morphologic analysis recovers the relationship among species of Sea and Cybdelis ; two subspecies of Cybdelis are restituted to species and a new subspecies of Sea sophronia is described.